Implementation and Resource Optimization of an Oral Anticancer Medication Clinical Pharmacy Trainee Program: Operational and Financial Impact at a Tertiary Cancer Centre - Christine Peragine; Flay Charbonneau; Susan Singh; Carlo DeAngelis (Current Oncology, 2026)
Background: The emergence of oral anticancer medications (OAMs) has increased demand for specialized clinical pharmacy services (CPSs). Concurrently, Canadian cross-sectional data highlights undergraduate education gaps, with fewer than 14% of community pharmacists reporting adequate training on OAM therapies. We designed, implemented, and evaluated a pharmacist-led Oral Anticancer Medication Clinical Co-op Program (OAMCCP) to bridge this experiential education gap while cost-effectively expanding institutional capacity. Methods: Launched in Fall 2022, the OAMCCP integrated one PharmD student per 16-week term into a multidisciplinary oncology specialty pharmacy. Trainees executed core ambulatory oncology clinical pharmacy key performance indicators (AOcpKPIs), including Best Possible Medication Histories (BPMHs), drug–drug interaction (DDI) screenings, and proactive adherence and toxicity follow-up. Student competency was verified by a licensed oncology pharmacist to maintain patient safety. Impact was quantified via self-reported task logging over 15 weeks, standardized 10-point patient satisfaction surveys, payroll expenditure comparisons, and student testimonials. Results: Trainees completed 673 clinical tasks (~45 tasks/week), contributing 16.2 h of direct clinical support weekly—effectively adding +0.43 full-time equivalent (FTE) to service capacity. Mean patient satisfaction was 9.5/10 (n = 29), with students successfully managing inquiries in 96.5% of encounters. Financially, a 1.0 FTE student (44,700 CAD/year cost) captured clinical capacity valued at 69,300 CAD/year (0.43 FTE pharmacist equivalence). Conclusions: The OAMCCP resolves experiential training gaps while presenting a safe, scalable, and financially viable human resource framework that expands oncology pharmacy services.